Tradução e adaptação cultural das escalas Amputee Mobility Predictor (AMP) e Houghton Scale of Prosthetic use – escalas preditoras da mobilidade em amputados de membros inferiores - Almeida, Ananda Oliveira (2017)
Introduction: Amputation is a surgical procedure characterized by total or partial removal of one or more limbs. In Brazil, amputations have an incidence of 13.9 per 100,000 inhabitants, of whom 85% are lower limbs. Amputees increasingly rely on a variety of assisted technologies to collaborate in the process of social rehabilitation, among which we can mention prostheses. Despite the benefits of this technology, it is observed that there is an underutilization of it. Therefore, the purpose of this study is to translate and culturally adapt the AMP and Houghton scales to Brazilian Portuguese. Methods: The steps of translation and cultural adaptation followed the instructions of the COnsensus based Standards for the selection of health status Measurement INstruments (COSMIN). The process involved three stages: the first one was attended by two bilingual physiotherapists who generated two independent translations of the AMP and Houghton scales (T1 and T2), the second stage consisted of the junction of these two translations, generating the version T1 & 2 that had been applied By three physiotherapists in three patients over 18 years of age and those with amputees in order to evaluate the level of comprehension of the scales, the third step was to modify the T1 & 2 version after the comments of the three physiotherapists. Results: The comprehension level questionnaires answered by the physiotherapists showed that, for the most part, the items were comprehensible. Discussion: Data from the analysis showed that most physiotherapists attributed a good understanding to Houghton and AMP items, even though they identified possible suggestions to improve AMP assessment, through suggestions and comments to adapt some items without change the meaning of the original version. Conclusion: The Brazilian versions of the AMP and Houghton scales may be applied in research to identify the causes that corroborate the underuse of amputee prosthesis.